FELTARBEJDETS FORPLIGTELSER: Deltagelse og kritik blandt sateré-mawé-immigranter i Manaus, Brasilien - Groes-Green, Christian (Tidsskriftet Antropologi, 2002)
Current studies of human poverty and suffering seem to lack reflexivity on the kinds of alternatives or solutions that might be found in the local context of study. By reference to experiences from fieldwork among indigenous Sateré-Mawé immigrants in Manaus, Brazil it is illustrated how “participation” as an anthropological method is more than a tool for collecting ethno-graphic data. It is a practice like any other, involving social obligations towards our informants and a necessary engagement in the field of study. As an inseparable part of the production of anthropological know-ledge this engagement should be more explicitly addressed and reflected in anthropological writing and in the very idea of the anthropological project. If this engagement is properly reflected and addressed, a constructive anthropological critique might evolve that points to viable solutions to the social problems and sufferings encountered. Re-inscribing “participation” in the anthropological project as fundamental to any knowledge might also remind us that fieldwork, like any other social engagement, is fraught with social obligations that do not vanish with theoretical distance and abstraction.